Scientific and Theoretical Foundations of Ensuring the Economic Stability of Family Businesses (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes the scientific and theoretical foundations of ensuring the economic stability of family businesses. The social and economic significance of family entrepreneurship, its role in the national economy, as well as methodological approaches and strategies used to achieve stability are studied. The article considers such important factors in the effective functioning of family businesses as financial resource management slot zeus, innovation approaches, state support system, and adaptation to market conditions. At the same time, the impact of state policy on family business and practical strategies used to ensure economic stability are also analyzed